2020
DOI: 10.22342/jme.11.3.11846.417-438
|View full text |Cite
|
Sign up to set email alerts
|

Deductive or Inductive? Prospective Teachers’ Preference of Proof Method on an Intermediate Proof Task

Abstract: The emerging of formal mathematical proof is an essential component in advanced undergraduate mathematics courses. Several colleges have transformed mathematics courses by facilitating undergraduate students to understand formal mathematical language and axiomatic structure. Nevertheless, college students face difficulties when they transition to proof construction in mathematics courses. Therefore, this descriptive-explorative study explores prospective teachers' mathematical proof in the second semester of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 29 publications
2
9
0
3
Order By: Relevance
“…The results of the study could be summarized that the deductive method and online exercises were effective in developing students' learning achievement of mathematic relations. The results of the study confirm the benefits of the deductive learning management in math education as found in the previous studies (e.g., Atta et al, 2015;Ayalon & Even, 2008;Rahmah, 2017;Singh, 2017;Sriplaeg, 2022;Siswono et al, 2020). At this point, apart from developing students' knowledge of the area (Singh, 2017), mathematical problem-solving (Rahmah, 2017), and solving intermediate proof tasks (Siswono et al, 2020), the deductive learning management was also capable of improving students' knowledge of mathematical relation.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results of the study could be summarized that the deductive method and online exercises were effective in developing students' learning achievement of mathematic relations. The results of the study confirm the benefits of the deductive learning management in math education as found in the previous studies (e.g., Atta et al, 2015;Ayalon & Even, 2008;Rahmah, 2017;Singh, 2017;Sriplaeg, 2022;Siswono et al, 2020). At this point, apart from developing students' knowledge of the area (Singh, 2017), mathematical problem-solving (Rahmah, 2017), and solving intermediate proof tasks (Siswono et al, 2020), the deductive learning management was also capable of improving students' knowledge of mathematical relation.…”
Section: Discussionsupporting
confidence: 89%
“…They are also allowed to test their understanding of the concept via exercises that could ensure their development of skills and abilities. The benefits of the deductive method in teaching mathematics could be seen in several studies (e.g., Atta et al, 2015;Ayalon & Even, 2008;Rahmah, 2017;Singh, 2017;Sriplaeg, 2022;Siswono et al, 2020).…”
Section: ) Application Stagementioning
confidence: 96%
“…For this reason, we agree with Ubuz and Yayan (2010) when stating that "an important step to improving subject matter knowledge should be better subject matter preparation for primary teachers" (p. 799). We also believe that addressing difficulties in the content knowledge of primary-school teachers (see, for instance, Oflaz, Polat, Altaylı Özgül, Alcaide, & Carrillo, 2019) would shed light on where to focus so that teachers to acquire essential content knowledge to teach in the various mathematical domains (regarding proving as mathematical content, see, for instance, Siswono, Hartono, & Kohar, 2020;van Dormolen, 1977). In this way, studying teachers' activities when they strive either to prove mathematical assertions or to formulate conjectures constitutes the first step and exploring the reasons behind the difficulties found when conjecturing and proving would be an interesting topic for further research.…”
Section: Some Reflections On the Resultsmentioning
confidence: 99%
“…Action proof is one way to develop the basic skills needed in mathematics in the last 20 years (Wittmann, 2021). Besides, it takes time to understand and broad skills and knowledge to prove a fact (Siswono et al, 2020). This happens in every step process carried out by students to arrive at the correct statements and conjectures.…”
Section: Discussionmentioning
confidence: 99%